Design of Multipoint Temperature and Humidity Silverware Forging for Engraving Process Measurement System Based on ZigBee Technology - Jinye Wei; Jiaqian Leng (My University, 2022)
This paper studies an embedded monitoring system centered on ZigBee technology to realize real-time temperature and humidity monitoring, and to ensure low power consumption, high reliability, low cost, and collection of environmental information. The communication is designed using the star topology, and the whole network structure is composed of a master node and three sensor receiving nodes to realize the unlimited transmission of network data. The main control point is to determine the coordination of the scope of the ZigBee network configuration system. The ZigBee network can communicate with the host through the data port to realize the acceptance of temperature and humidity data and the sending of commands. Based on this research, this paper determines the impact of non-target parameters on the actual measurement data of the multipoint temperature and humidity sensor, and at the same time determines the key influencing factors. For HMP-45D multipoint temperature and humidity, an improved genetic algorithm (GA) combined with a support vector machine (SVM) is used to compensate humidity and temperature data, which is designed to affect the actual measurement error of the multipoint temperature and humidity sensor. This paper studies the silver forging process, compares the environmental factors of silver carving, further puts forward the control strategy of Hagoun product forging and carving environment control from the perspective of temperature and humidity, and designs the environmental temperature and humidity measurement and control system from the perspective of temperature and humidity control. The system design proposed in this paper is mainly to construct and apply the silverware forging and engraving environment temperature and humidity measurement and control system on the basis of integration and maintenance-free and verify the effectiveness and feasibility of the system in the protection of cultural relics.
Keywords: Advanced Chemical Sensor Technologies